Fenomena Money Politics Dalam Pemilu Di Kabupaten Bireuen Tahun 2024 Studi Hukum Positif Dan Fiqh Siyasah - Muhammad Zikri; Bukhari Ali; Azmil Umur (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of money politics in elections remains a serious challenge to the integrity of democracy and the implementation of Islamic values in Bireuen Regency, where Islamic law is formally upheld. Although elections are normatively conducted based on the principles of honesty and fairness, the practice of vote buying through monetary or material incentives continues to occur and is often perceived as normal within the local political culture. This study aims to analyze money politics in Bireuen elections from the perspective of positive law and fiqh siyasah (Islamic political jurisprudence). The research employs a qualitative descriptive approach using juridical-normative and socio-empirical methods, as well as Islamic jurisprudential analysis. Data were collected through literature review, field observation, and in-depth interviews with election officials, community leaders, voters, and related stakeholders. The findings reveal that under Indonesian positive law, money politics constitutes an electoral crime as stipulated in Law Number 7 of 2017, yet its enforcement remains weak due to limited evidence and low public participation in reporting violations. From the perspective of fiqh siyasah, money politics is categorized as risywah (bribery), which is strictly forbidden in Islam, as it undermines the principles of shura (consultation), justice, and trustworthiness in leadership. The study recommends an integrated approach combining legal enforcement, political education, and the active role of religious figures to foster voters’ moral awareness in order to realize clean and Islamic-based elections.